Etiquette for educational counselors - Kazem, Majed Abed Jawad (Al-Adab Journal, 2022)
To identify the etiquette of educational counselors from the General Directorates of Education in Baghdad, and to achieve the goal of the research, the etiquette scale was built based on the theory of self (Carl Rogers) of (20) paragraphs, and it was applied to the research sample of (200) by (80) counselors and (120) A guide and two types of honesty were extracted, 1- apparent honesty 2- and constructive honesty. The reliability coefficient reached (0.81) and (0.83) by the Facronbach method, and one of the results is that the research sample has a high level of etiquette.